2017
DOI: 10.1002/dc.23686
|View full text |Cite
|
Sign up to set email alerts
|

The value of the UroVysion® FISH assay in the risk‐stratification of patients with “atypical urothelial cells” in urinary cytology specimens

Abstract: U-FISH allows risk stratification in patients with AUC. However, its usefulness is diminished by the high false-positive rate, making it important to interpret U- FISH results in the patient's clinical context. Diagn. Cytopathol. 2017;45:481-500. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 77 publications
1
19
0
Order By: Relevance
“…Similar to the current study, Virk et al found high specificity of FISH when applied to cases diagnosed as AUS . Miki et al, however, found high specificity of FISH in their cases originally diagnosed as atypical, but extremely low specificity when using the TPS definition of AUS . It should be noted, however, that within our particular cohort no cases representative of HGUC were diagnosed as atypical.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar to the current study, Virk et al found high specificity of FISH when applied to cases diagnosed as AUS . Miki et al, however, found high specificity of FISH in their cases originally diagnosed as atypical, but extremely low specificity when using the TPS definition of AUS . It should be noted, however, that within our particular cohort no cases representative of HGUC were diagnosed as atypical.…”
Section: Discussionsupporting
confidence: 84%
“…24 Miki et al, however, found high specificity of FISH in their cases originally diagnosed as atypical, but extremely low specificity when using the TPS definition of AUS. 25 It should be noted, however, that within our particular cohort no cases representative of HGUC were diagnosed as atypical. Unlike these studies, however, we sought to evaluate the performance in the context of individual morphological features.…”
Section: Discussionmentioning
confidence: 62%
“…Therefore, accurate assessment of the N/C ratio close to cutoffs is a key training objective and should be emphasized in continuing education or training programs related to TPS. In addition, employment of ancillary tests, such as immunocytochemistry for p16 and Ki-67 or Urovysion fluorescence in situ hybridization (FISH), may help improve the risk stratification in the intermediate group [24,25]. A combination of cytomorphological assessment and ancillary testing would provide more accurate results for patient management.…”
Section: Discussionmentioning
confidence: 99%
“…Even in such clinical circumstances, one should be cognizant of false-positive results, which can arise from tetraploid umbrella cells and polyomavirus cytopathic changes. 5 In a study by Virk et al, 6 the sensitivity of UroVysion was reported to be 44.6% and the false-positive rate to be 53% in equivocal urine cytology cases. In addition, it is noteworthy that in cases of equivocal urine cytology, a negative UroVysion test does not rule out low-grade or high-grade urothelial carcinoma.…”
Section: Discussionmentioning
confidence: 98%